ANALISIS KIMIA BEBERAPA JENIS KAYU INDONESIA - Gustan Pari; Fityani B Lestari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Chemical analyses of several Indonesia wood from West Java and Kalimantan has been conducted. The chemical component tested consisted of holocellulose, cellulose, lignin, pentosan, ash and silica content, solubility in cold water, hot water, one percent sodium hydroxide and alcohol benzene extractrive.The result shows that the holocellulose content ranges from 57,95 - 61,97 percent, cellulose from 40,93 - 57,41 percent, lignin from 22,01 - 29,00 percent, pentosan from 8,35-21,50 percent, ash content from 0,18 - 3,64 percent, silica content from 0,05 - 2,47 percent. The solubility in cold water ranges from 0,39 - 3,59 percent, hot water from 0,56 - 9,48 percent, in one percent sodium hydroxide from 6,25 - 31,68 percent and in alcohol benzene (1:2) from 0,95 - 6,03 percent.